PENGARUH FASILITAS BELAJAR TERHADAP HASIL BELAJAR EKONOMI DI KELAS XI IIS 2 MA MATHLA’UL ANWAR PONTIANAK - Malasari, Malasari; Ulfah, Maria; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study entitled the influence of learning facilities on economic learning outcomes in the class XI IIS 2 MA Mathla’ul Anwar Pontianak. The problem in this research is whether the influence of learning facilities on the results of economic learning in the class XI IIS 2 MA Mathla’ul Anwar Pontianak. The method used in this research is descriptive method percentage with form of research ex post facto. Population in this study amounted to 24 students of class XI IIS 2. Data obtained by using the technique of direct communication with the tool in the form of observation sheet or checklist list, indirect communication techniques with tools in the form of questionnaires and documentary techniques with tools in the form of research photographs. Based on data analysis techniques in get the regression equation Y = 98,793 + 0,590X. t test results show that the value of tarithmetic > ttable (4,280 > 0,291). While the value of coefficient of destraction R2 equal tu 0,050 which means the percentage contribution of learning facilities to the results of economic learning in class XI IIS 2 MA Mathla’ul Anwar Pontianak by 50%.Keywords : Learning Facilies, Learning Outcomes Economic